The falcon's feather eaudiobook - Trueit, Trudi (Explorer Academy, 2019)
It's an adventure of a lifetime when Cruz Coronado sets sail aboard the Explorer Academy ship to continue his studies at sea. But, things take a turn while exploring the icy north, when he embarks on a dangerous mission to uncover the first piece of an important puzzle his mother left behind. In the exciting follow-up to The Nebula Secret in the 7-book Explorer Academy series, Cruz, Sailor, and Emmett, along with their new ally Bryndis, embark on their first globe-trotting mission aboard the ship Orion . Cruz jumps right back into school and starts using the latest technology in submersible underwater dives, but is soon reminded of the dangers of exploration when his equipment fails and he almost drowns. Determined to keep his eyes on the prize, Cruz sneaks away to try to find answers, but unknowingly lures his friends into bigger trouble. When a friend of Cruz's mom meets an untimely end, Cruz's luck really seems about to run out and the questions multiply. What does the message mean? Where will it lead? Who is following him? And why? This captivating book is the sequel every Explorer Academy fan is waiting to read!